2016
DOI: 10.1103/physrevd.94.024048
|View full text |Cite
|
Sign up to set email alerts
|

Accumulative coupling between magnetized tenuous plasma and gravitational waves

Abstract: We explicitly compute the plasma wave (PW) induced by a plane gravitational wave (GW) travelling through a region of strongly magnetized plasma, governed by force-free electrodynamics. The PW co-moves with the GW and absorbs its energy to grow over time, creating an essentially force-free counterpart to the inverse-Gertsenshtein effect. The time-averaged Poynting flux of the induced PW is comparable to the vacuum case, but the associated current may offer a more sensitive alternative to photodetection when des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, according to contemporary observations, there are very widespread background galactic magnetic fields (GMFs, strength around ∼ 10 −10 to 10 −9 Tesla) [28] within the Milky way. Therefore, according to the electrodynamics in curved spacetime, in the frame of EM response to GWs, we propose that such high-frequency GWs of sub-solar mass PBH binary mergers will interact with the GMFs in the Milky The effect of EM response to GWs had been long studied [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and previous works [30,[35][36][37]45] indicated that the strengths of perturbed EMWs depends on both strengths and spatial scales (accumulation distance) of the background magnetic fields. Thus, the GMFs will provide a huge accumulation distance to compensate the weakness of their very low strengths, and then would lead to considerable EM signals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, according to contemporary observations, there are very widespread background galactic magnetic fields (GMFs, strength around ∼ 10 −10 to 10 −9 Tesla) [28] within the Milky way. Therefore, according to the electrodynamics in curved spacetime, in the frame of EM response to GWs, we propose that such high-frequency GWs of sub-solar mass PBH binary mergers will interact with the GMFs in the Milky The effect of EM response to GWs had been long studied [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and previous works [30,[35][36][37]45] indicated that the strengths of perturbed EMWs depends on both strengths and spatial scales (accumulation distance) of the background magnetic fields. Thus, the GMFs will provide a huge accumulation distance to compensate the weakness of their very low strengths, and then would lead to considerable EM signals.…”
Section: Introductionmentioning
confidence: 99%
“…proposed here based on the effect of EM response to GWs, which had been long studied [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] but were usually in very high frequency bands such as over GHz (10 9 Hz) [28][29][30][31][32][33][34][35][36][37][38][39]. Whereas, we now apply such mechanism targeting on the GWs in the intermediate band (around ∼ 10 1 to ∼ 10 3 Hz) from the binary mergers.…”
mentioning
confidence: 99%